The Adat Contributions for the Villages to Develop Independently: Cases from the Kei Islands, Southeast Maluku Regency - P.M. Laksono (Humaniora, 2016)
Eventhough the district government has somehow acknowledged the failure of its own initiatives to empower its people, there must have been certain creativities or custom-related wisdom which seem to be able to independently respond to any development initiative. Precisely this article is trying to track creative moments when the customs and people writhing on the “bottom” of formal structures to contribute for a self modernization. Data from a short ethnographic study in the Kei Islands in mid 2016 shows the complicated moments of how indigenous communities survive while appropriating opportunities (friction) that is open due to failure of both the government and the market penetration to radically change the identity of indigenous local communities. Hence, modernization does not happen in a vacuum culture. Through their primordial taste, i.e. their identity, traditional leaders, businessmen and ordinary citizens creatively appropriating moments linkage to the world to declare local social differences.